Model Strategi Pengembangan dan Keberlanjutan Kampung ‎Angklung Ciamis Menjadi Desa Wisata Berbasis ‎Pemberdayaan Masyarakat - Yuditha, Devina; Iskandar, Hari (Universitas Mataram, 2024)
The diversity of each tribe in Indonesia is the main attraction as a tourist destination for both local and foreign tourists. The development of tourism based on local culture and community can be a long-term opportunity for an area because each region has natural resources, people and local knowledge that are of positive value for the development of tourist destinations in the area. Kampung Angklung Ciamis is located in Panyingkiran Village and is an area where local community activities are angklung craftsmen who are quite productive in making angklung so that it has the potential to become a tourist village. But there are several obstacles to making Angklung Village into a tourism village so that a development strategy is needed and what is used is the analysis of the 6A component of Tourism, SWOT analysis, and the application of the concept of community-based tourism (CBT). This research is descriptive qualitative research, with the subjects being the manager, the head of the community of craftsmen and musical arts, angklung distributors and the people of Ciamis Angklung Village. Data collection techniques are carried out by interviews, observation, and documentation. The technique of determining the resource person uses Purposive Sampling. The data analysis method uses three, namely data reduction, data presentation, and conclusion drawing / verification. The results of this study show that Angklung Ciamis Village needs regional development in order to become a community-based cultural tourism village.The results of IFAS and EFAS show that the development strategy of Angklung Ciamis Village is in Quadrant I (Growth Oriented Strategy), namely the strength and also the opportunity to obtain maximum development.The implementation of the tourism village concept requires several efforts such as structuring tourist areas, determining tourist products and attractions, developing tourist facilities, marketing and partnership, and empowering the community.